Motivacija za postignućem i opšti stav o vrijednostima sporta / Achievement Motivation and the General Attitude towards Sport Values - Popadić, Bojana; Ćorluka, Bojan (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
This paper deals with the research of relations between achievement motivation and the general attitude towards sport values in case of sportsmen (basketball, football and volleyball players). On the basis of the results, we have determined the distribution of the general attitude towards sport values, as well as the relation between achievement motivation and the general attitude towards sport values. Examinees with bold achievement motivation have positive general attitude, they are ready to strive efforts in order to improve their sports results, and they tend to achieve the set, clearly defined and high enough goals. We have noticed that achievement motivation has an important role in the attitude towards sport values. When it comes to achievement motivation, it is very important to know that persons with tendencies towards competition and/or achieving the goal probably would not be successful without developed characteristic of being determined, patient and oriented towards planning. Both psychologists and trainers in the process of sportsmen preparation should be familiar with this fact. The development and fulfilment of acheivment motives through sport activities provide filfilment of many other motives important for relasiation of personal needs, and the engagement in sport and the general postive attitude towards sport vaules.